Build Cultural Responsiveness: Integration Model Cross Element PAI Co Curricular with Minangkabau Ethnography - Silvia Susrizal; Syahrur Ramli; Susi Ratna Sari; Gusrina Fadhila; Demina (ISTAWA, 2025)
This study aims to develop a co-curricular integration model of Islamic Religious Education across elements based on Keminangkabauan ethnography to build...cultural responsivenesson students. The research method used isresearch and development(R&D) by adopting the ADDIE model (Analyze, Design, Development, Implementation, EvaluationThis research was conducted at MTsN 6 Lima Puluh Kota, West Sumatra. The results of the research produced a PAI co-curricular module integrated with four sub-themes of Minangkabau ethnography:Alua Jo Sambah(integration of Islamic values of law and contemplation with honesty, politeness and ethics),Marandang(integration of Islamic values of ta'awun and halal haram with mutual cooperation, cooperation and health), Blessings for the Village (integration of Islamic texts with the harmony of nature and the environment), as well asScars (cross-element performing arts, namely faith, morals, worship, and Minangkabau ethnography in theater, drama, and dance). Expert validation of the teaching module obtained an average score of 93% (very valid), while the practicality test by educators reached 92.6% (very practical). This model has proven effective in transforming normative Islamic values into contextual and culturally relevant learning experiences, thereby strengthening students' cultural responsiveness. However, the study also highlighted the need for a balance between cultural approaches and strengthening students' existential navigation skills so that Islamic Religious Education learning is not only a socialization of tradition, but also fosters independent thinking in facing global diversity.